Implementation of Corporate Social Responsibility of Sustainable National Project Companies - Anas Firmanto; Dewi Astutty; Diah Ayu Wisnu Wardhana (Innovation Business Management and Accounting Journal, 2025)
This study aims to analyze the implementation of corporate social responsibility (CSR) by companies that contribute to communities directly affected by sustainable national development projects and identify legal obstacles to its implementation. The research was conducted at the location of the infrastructure project managed by PT Hutama Karya Infrastruktur. The method used is empirical legal research with direct observation techniques, interviews, and case studies to obtain data on CSR practices implemented. The results showed that PT Hutama Karya Infrastruktur has implemented a CSR program that includes community empowerment, social infrastructure development, and environmental protection, such as the construction of public facilities, reforestation, and support for local Micro, Small and Medium Enterprises (MSMEs). However, challenges remain, particularly in aligning company policies with community needs and weak government oversight. Therefore, this study recommends strengthening government regulations and oversight mechanisms and increasing transparency and active community involvement in CSR planning and implementation. Companies can contribute more consistently to inclusive and responsible sustainable development with this approach.